Joint energy and spinning reserve scheduling integrating uncertain wind power - Govardhan, Manisha (2016 IEEE Students' Conference on Electrical, Electronics and Computer Science (SCEECS), 2016)
Classic unit commitment (UC) is an important and challenging task of allocating generating units subject to basic constraints over a scheduled time horizon to obtain the least generation cost. Penetration of wind power generator in a modern power system makes generation planning more complex. This study presents the effect of uncertain wind power on joint energy and spinning reserve scheduling. An inconsistent nature of wind speed and wind power is characterized by the Weibull probability distribution function considering overestimation and underestimation cost of the stochastic wind power. The effectiveness of the proposed approach is acknowledged from the results on an IEEE 10 unit system using modified Teaching-learning based optimization (MTLBO) algorithm which confirms a significant techno-economic saving.